A Dual‐Carbon Phase‐Modified and Nanostructured Nickel Sulfide Anode for Sodium‐Ion Batteries. Issue 4 (9th January 2017) - Han, Fei; Tan, Clara Yi Jun; Gao, Zhiqiang
Abstract: On the basis of the concept of a nanoconfinement reaction, a synthetic strategy was developed to construct ultrathin carbon‐film‐coated and nanostructured nickel sulfide anchored on carbon nanotubes (CNTs). The synthesis involved the direct growth of nickel hydroxide on the CNTs followed by dehydration, sulfidation, and carbon coating. If used as an anode material in sodium‐ion batteries (SIBs), the nickel sulfide‐based anode showed a high utilization rate of the active material and a favorable specific capacity of 390 mAh g −1 . The excellent performance of the nickel sulfide‐based anode in SIBs demonstrates the potential of nickel sulfide to be used as the anode material in SIBs if it is engineered to alleviate its structural constraints. In principle, this strategy can be conveniently adapted to engineer other transition‐metal‐based materials for applications in energy storage. Abstract : Just a little nick : A synthetic strategy is developed to construct dual‐carbon phase modified and nanostructured nickel sulfide. If used as an anode material in a sodium‐ion battery, the nickel sulfide based anode gives a specific capacity of 390 mAh g −1 and has excellent cycle life.